Satirical Narrative Processing: Examining the Roles of Character Liking and Media Enjoyment on Narrative-Consistent Attitudes. (21st March 2018) - LaMarre, Heather L; Grill, Christiane
Abstract: This study uses online survey data ( n = 127) with an embedded media manipulation to examine relationships between character liking, media enjoyment, and narrative consistent attitudes with late-night political comedian, Stephen Colbert's satirical campaign finance narrative. The data offer empirical support for the notion that narratively structured political satire processing models should consider relevant entertainment psychology and narrative persuasion concepts such as how audiences respond to the main characters and the role enjoyment plays in the process. Using structural equation modeling, media enjoyment significantly mediated the relationship between character liking and narrative consistent attitude formation (about the antagonist), but appears to have functioned as a suppressor variable. Competing models are offered in anOnline Appendix .